Highly Efficient Production of Nanoporous Block Copolymers with Arbitrary Structural Characteristics for Advanced Membranes - Guo, Leiming; Ntetsikas, Konstantinos; Zapsas, Georgios; Thankamony, Roshni; Lai, Zhiping; Hadjichristidis, Nikos (Angewandte Chemie International Edition, 2023)
The great significance of boosting the design of percolating nanopore structures in block copolymers (BCPs) for various cases has been widely demonstrated in the past several decades. However, it still remains challenging to prepare the desired porous structures in a rapid, facile, and universal manner. Here we have developed an unconventional and benchtop strategy to rapidly generate the nanoporous polystyrene‐based BCPs with arbitrary structural characteristics regardless of the BCP bulk morphology. This universal pore‐forming strategy enables the sustainable CO2‐based BCPs to form advanced membranes after 1 s soaking for efficiently rejecting 94.2 % brilliant blue R (826 g mol−1). Meanwhile, the water permeance retains around 1020 L (m2 h bar)−1, which is 1–3 orders of magnitude higher than that of other membranes. This strategy may offer an excellent opportunity to introduce percolating pore structures in those newly developed BCPs with which the previously reported pore‐forming methods may not deal. A new pore‐forming strategy has been developed for the fabrication of nanoporous block copolymers (BCPs) with arbitrary structural characteristics with 1 s soaking. This rapid, facile, and universal strategy can produce percolating nanopore structures in the polystyrene‐based BCPs with various bulk morphologies, which inspires us to prepare advanced membranes derived from the CO2‐based sustainable BCPs for fast molecular separation for the first time.